2008
DOI: 10.1016/j.ygyno.2008.01.042
|View full text |Cite
|
Sign up to set email alerts
|

A novel indole ethyl isothiocyanate (7Me-IEITC) with anti-proliferative and pro-apoptotic effects on platinum-resistant human ovarian cancer cells

Abstract: Objective-A novel indole-ethyl isothiocyanate derivative (7Me-IEITC) was defined as a potent growth-suppressing agent to cell lines derived from ovarian cancers. Key mechanisms of the cellular response in vitro were studied and suggest a potential of 7Me-IEITC as a therapeutic drug.Methods-The viability of ovarian cancer cell lines (SKOV-3, OVCAR-3) in comparison to pancreatic and prostate cancer cell lines, primary fibroblast and immortalized trophoblasts after treatment with 7Me-IEITC was analyzed. Morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The DTP at the NCI maintains a public accessible database of cytotoxic drugs; a comparison analysis (COMPARE) of known cytotoxic drugs versus NB7M indicated that NB7M is more potent than a variety of clinically relevant drugs, such as cisplatin, oxaloplatin, seliciclib, CNDAC, 5-FU and cyclophosphamide, in most of the NCI 60 cell lines but is less potent than docetaxel, adriamycin and gemcitabine. Our in vitro investigations have shown that NB7M and its synthetic parent compound 7Me-IEITC show overlapping cytotoxic effects with ovarian cancer cell lines OVCAR-3 and SKOV-3 being more sensitive to NB7M as compared to 7Me-IEITC (present manuscript; Singh et al, 2008). This also applies to several neuroblastoma cell lines, while the viability of lung fibroblasts or trophoblast cell lines by either compound is only marginally affected Brard et al, 2008).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The DTP at the NCI maintains a public accessible database of cytotoxic drugs; a comparison analysis (COMPARE) of known cytotoxic drugs versus NB7M indicated that NB7M is more potent than a variety of clinically relevant drugs, such as cisplatin, oxaloplatin, seliciclib, CNDAC, 5-FU and cyclophosphamide, in most of the NCI 60 cell lines but is less potent than docetaxel, adriamycin and gemcitabine. Our in vitro investigations have shown that NB7M and its synthetic parent compound 7Me-IEITC show overlapping cytotoxic effects with ovarian cancer cell lines OVCAR-3 and SKOV-3 being more sensitive to NB7M as compared to 7Me-IEITC (present manuscript; Singh et al, 2008). This also applies to several neuroblastoma cell lines, while the viability of lung fibroblasts or trophoblast cell lines by either compound is only marginally affected Brard et al, 2008).…”
Section: Discussionsupporting
confidence: 51%
“…The growth of IGROV1, OVCAR-3, OVCAR-5 was highly affected by 10 mM of the drug (as shown for OVCAR-3 in the cytotoxicity assay performed in our laboratory) and OVCAR-8 and OVCAR-4 responded strongly to treatment, whereas SKOV-3 revealed less but still significant reduction in growth compared to the other five lines tested by the National Cancer Institute (NCI). Taken together, the NCI screen (http:// dtp.nci.nih.gov/screening.html) and our cytotoxicity assays suggest NB7M to be highly and specifically detrimental to cell lines derived from certain tumour types, including ovarian cancer, but less effective against other tumour types and marginally cytotoxic for control cell lines (e.g., TCL-1, HTR-8; Figure 1B and MRC-5 fibroblasts, Singh et al, 2008).…”
Section: Nb7m Shows Differential Effects On the Viability Of Various mentioning
confidence: 52%
See 1 more Smart Citation
“…1b) with increased in-vitro potency as compared to various naturally occurring ITC have been developed. Cytotoxic mechanisms of these compounds include rapid induction of apoptosis, alteration of Mitogen activated protein kinase (MAPK) signaling and cell-cycle inhibitory effects in neuroblastoma [12,13] and ovarian cancer cells [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous structure-activity guided modification of PEITC to identify potent ITC derivatives [12,14,15], in the present manuscript we describe a de novo approach to the structural optimization of PHITC, a synthetic longer chain congener of naturally occurring PEITC leading to the design of Abietyl-Isothiocyanate (ABITC) (Fig. 1c).…”
Section: Introductionmentioning
confidence: 99%